Factorial validity, measurement and structure invariance of the Malay language decisional balance scale in exercise across gender. - Garry Kuan; Abdulwali Sabo; Sukanlaya Sawang; Yee Cheng Kueh (PLoS ONE, 2020)
BACKGROUND:This study examined the psychometric properties of the Malay version of the decisional balance (DB-M) for exercise (i.e. perceived benefits and perceived barriers) using a cross-sectional design. Also, this study assessed the measurement and structural invariance of the DB-M across gender. METHODS:The study sample consisted of 750 students (female: 51.7%, male: 48.3%), with a mean age of 20.2 years (SD = 1.2). Decision balance (DB) scale was assessed with the 10-item DB-M. Standard forward-backward translation was performed to translate the English version of the DB into Malay version (DB-M). RESULTS:The confirmatory factor analysis (CFA) results based on the hypothesised measurement model of two factors and ten items demonstrated adequate factor structure after the addition of some correlated item residuals (comparative fit index (CFI) = .979, Tucker and Lewis index (TLI) = .969, standardised root mean square residual (SRMR) = .037, root mean square error of approximation (RMSEA) = .047). The construct reliability and average variance extracted values were .850 and .839, and .542 and .538, for perceived benefits and perceived barriers, respectively. Meanwhile, the Cronbach's alpha was .857 and .859, and the intraclass correlation coefficient for test-retest reliability was .979 and .960 for perceived benefits and perceived barriers respectively. The findings provided evidence for measurement invariance of DB-M for the male and female samples. The final CFA model fit the data well for both male sample (CFI = .975, TLI = .964, SRMR = .040, RMSEA = .052) and female sample (CFI = .965, TLI = .949, SRMR = .044, RMSEA = .058). CONCLUSIONS:The translated version of the DB-M was valid and reliable for assessing the level of perceived benefits and perceived barriers in exercise among university students in Malaysia.